Diversity and long-term environmental benefits of an urban afforestation project in the Philippines - Tolabing, Hans Diether F. (Department of Biology and Environmental Science, College of Science, University of the Philippines Cebu, 2022)
The ongoing climate crisis and biodiversity loss have put forward tree planting projects as potential ecosystem-based solutions. These projects provide ecosystem services in the form of carbon sequestration, air pollutants removal, and flood regulation, which makes them ideal in urban areas. The Ayala Carbon Forest (ACF) is an afforested site in Cebu City. Cebu City is a highly urbanized area in the Philippines and has high carbon and air pollutant emissions. This study aims to: assess the biodiversity of the ACF through a field survey; estimate its environmental benefits provided to Cebu City using the i-Tree Planting Calculator; and, determine factors that significantly affect the environmental benefits using stepwise regression modeling. Results indicate that there are at least 43,623 trees in ACF which belong to 34 families and 111 species. The most abundant species is Pterocapus indicus, a critically endangered species. Both the tree diversity and species dominance of the ACF are low at 1.29 and 0.23, respectively. Assuming the trees receive full sun exposure, the ACF is projected to sequester up to 320,000 tonnes CO2, 420 tonnes O3, 273 tonnes SO2, 72 tonnes PM 2.5, and 32 tonnes NO2 by 2070. It is also projected to intercept up to 6.3 million m3 of rainfall and avoid 230,000 m3 of runoff. However, these environmental benefits are not enough to mitigate the emissions and flooding of Cebu City. The stepwise regression analysis indicates that the biodiversity indices are not effective predictors of environmental benefits. Instead, there is a significant positive trend in the environmental benefits with increasing biomass and abundance of the ACF. Although the environmental benefits are insignificant, the ACF can still serve as a carbon sink and it illustrates the potential of afforestation projects when upscaled.